2016
DOI: 10.1007/s13202-016-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

Using high- and low-salinity seawater injection to maintain the oil reservoir pressure without damage

Abstract: The oil reservoir pressure declines due to oil production, and this decline will lead to reduction in the oil productivity. The reservoir pressure maintenance is a practice in the oil industry in which seawater is injected into the aquifer zone below the oil zone to support the reservoir pressure. Calcium sulfate scale is one of the most serious oilfield problems that could be formed in sandstone and carbonate reservoirs. Calcium sulfate may precipitate during the injection of seawater with high sulfate conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Barium, calcium, magnesium and strontium were also reported at higher concentrations than other metals in the samples at 594 mg/L (4.33 mM), 5434 mg/L (135.60 mM), 2005 mg/L (82.51 mM) and 633 mg/L (7.22 mM), respectively. These high metal concentrations remain within the range reported in other oil reservoir formation waters [39][40][41].…”
Section: Formation Water Chemistrysupporting
confidence: 84%
“…Barium, calcium, magnesium and strontium were also reported at higher concentrations than other metals in the samples at 594 mg/L (4.33 mM), 5434 mg/L (135.60 mM), 2005 mg/L (82.51 mM) and 633 mg/L (7.22 mM), respectively. These high metal concentrations remain within the range reported in other oil reservoir formation waters [39][40][41].…”
Section: Formation Water Chemistrysupporting
confidence: 84%
“…Seawater injection, amongst the other, is one of the most common EOR techniques for offshore oil fields [28] [29]. With time, the water fraction in the produced fluid can reach levels of 95% or higher, increasing the contact between tube materials and electrolyte [30].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various kinds of chelating agents, environmentally friendly compounds such as N -(2-hydroxyethyl)ethylenediamine- N , N′ , N′ -triacetic acid (HEDTA) and N, N -bis(carboxymethyl)- l -glutamic acid (GLDA) are well suited to chemical stimulation 31 , 32 . A previous study examined the use of HEDTA solution of pH 2.5, 4, and 9 to stimulate carbonates at approximately 150 °C, and reported that the use of HEDTA at pH 4 was effective 33 .…”
Section: Introductionmentioning
confidence: 99%